Residual Shoulder Motion Vector Projection - Losier, Yves; Englehart, Kevin; Hudgins, Bernard (CMBES Proceedings, 2008)
Providing an externally powered prosthetic solution for high-level upper extremity amputation cases requires several design factors to be considered by the clinical fitting team. The sensors used must often be finely adjusted during the prosthesis fabrication in order to provide consistent repeatable control input signals. The work presented in this paper introduces a mathematical framework capable of implementing robust residual shoulder motion driven control using only a short preliminary training protocol in an attempt to remove issues such as sensor type, alignment, and range of motion. The algorithm determines the output amplitude values based on the real time residual shoulder position to reliably drive the prosthetic limb’s actuators. This algorithm provides a new control input option for designing an externally powered prosthetic solution for high-level amputation cases.